2014
DOI: 10.7824/rbh.v13i3.273
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de biótipos de leiteiro com suspeita de resistência a herbicidas inibidores da ALS e Protox

Abstract: Resumo -Objetivou-se com o presente trabalho avaliar a confirmação da ocorrência de resistência de biótipos de leiteiro, oriundos de Rondônia e do Rio Grandes do Sul a herbicidas com diferentes mecanismos de ação, bem como determinar a dose dos herbicidas necessária para redução de 50% na massa seca das plantas (GR50) e para o controle de 50% das plantas de cada unidade experimental (C50). Para tanto foi instalado um experimento em casa de vegetação, em blocos casualizados, com quatro repetições. Os herbicidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
3
2
0
Order By: Relevance
“…There was no adjustment of the data to the model for the herbicide penoxsulam because the lower rates used in the experiment (0.03x and 1x) provided around 90% control of SAGMO. Prigol et al (2014) reported that Euphorbia biotypes suspected to be resistant to PROTOX and ALS inhibiting herbicides also did no showed data adjustments to the model used in implementing cloransulam-methyl on the weed assessed agreeing with the results of this study.…”
Section: Resultssupporting
confidence: 88%
“…There was no adjustment of the data to the model for the herbicide penoxsulam because the lower rates used in the experiment (0.03x and 1x) provided around 90% control of SAGMO. Prigol et al (2014) reported that Euphorbia biotypes suspected to be resistant to PROTOX and ALS inhibiting herbicides also did no showed data adjustments to the model used in implementing cloransulam-methyl on the weed assessed agreeing with the results of this study.…”
Section: Resultssupporting
confidence: 88%
“…Crossed resistance of wild poinsettia has already been shown by other studies MEROTTO, 1999;XAVIER et al, 2013;PRIGOL et al, 2014). Resistance to ALS-inhibiting herbicides was found for chemical groups of imidazolinones, sulfonylureas and triazolopyrimidines (PRIGOL et al, 2014), as observed by this study.…”
Section: Resultssupporting
confidence: 85%
“…Crossed resistance of wild poinsettia has already been shown by other studies MEROTTO, 1999;XAVIER et al, 2013;PRIGOL et al, 2014). Resistance to ALS-inhibiting herbicides was found for chemical groups of imidazolinones, sulfonylureas and triazolopyrimidines (PRIGOL et al, 2014), as observed by this study. Unsatisfactory control of biotypes 20.2 and 21.1 by ALS-inhibiting herbicides, associated with low resistance to the herbicide glyphosate, may even hinder its management in soybean crops since their mutual and abusive use may submit wild poinsettia plants to high selection pressure (TREZZI et al, 2011;COSTA;RIZZARDI, 2014).…”
Section: Resultssupporting
confidence: 85%
“…Regardless of the conditions adopted by different laboratories, the resistance levels and crossresistance patterns primarily depend on the population and its resistance mechanism. Euphorbia heterophylla resistant to PPO inhibitors is widespread across Brazilian agricultural areas, especially in the south (Prigol et al 2014;Trezzi et al 2006). Here, we demonstrate that R PPO is resistant to at least three chemical groups of PPO inhibitors (diphenyl ether, pyrimidinedione, and N-phenylphthalimid).…”
Section: Cross-resistance To Ppo Inhibitors In Euphorbia Heterophyllamentioning
confidence: 99%